2021
DOI: 10.3390/microorganisms9050887
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Novel Bacteria Capable of Degrading 1,4-Dioxane in the Presence of Diverse Co-Occurring Compounds

Abstract: Biodegradation is found to be a promising, cost-effective and eco-friendly option for the treatment of industrial wastewater contaminated by 1,4-dioxane (1,4-D), a highly stable synthetic chemical and probable human carcinogen. This study aimed to isolate, identify, and characterize metabolic 1,4-D-degrading bacteria from a stable 1,4-D-degrading microbial consortium. Three bacterial strains (designated as strains TS28, TS32, and TS43) capable of degrading 1,4-D as a sole carbon and energy source were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…1,4-Dioxane biodegradation is initiated by enzymes encoding soluble di-iron monooxygenase (SDIMO) genes. SDIMO genes also have the ability to catalyze the initial oxidation of a wide variety of hydrocarbons ( Li et al 2014 ; Inoue et al 2016 ; Tusher et al 2021 ). To date, three SDIMO gene clusters (Group-2, Group-5, and Group-6) have been confirmed to be involved in the metabolic biodegradation of 1,4-dioxane ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4-Dioxane biodegradation is initiated by enzymes encoding soluble di-iron monooxygenase (SDIMO) genes. SDIMO genes also have the ability to catalyze the initial oxidation of a wide variety of hydrocarbons ( Li et al 2014 ; Inoue et al 2016 ; Tusher et al 2021 ). To date, three SDIMO gene clusters (Group-2, Group-5, and Group-6) have been confirmed to be involved in the metabolic biodegradation of 1,4-dioxane ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“… Li et al (2014) found a positive correlation between the biodegradation of 1,4-dioxane and the abundance of Group-5 SDIMO genes, tetrahydrofuran/dioxane monooxygenase ( thmA/dxmA ). Genes thmA/dxmA also were identified in the 1,4-dioxane-metabolizing bacteria that belong to the genera Dokdonella, Afipia , and Pseudonocardia ( Inoue et al 2016 ; Tusher et al 2021 ) ( Table 2 ). Similarly, tetrahydrofuran monooxygenase gene cluster ( thmADBC ) was expressed by Pseudonocardia dioxanivorans CB1190 during growth on 1,4-dioxane ( Grostern et al 2012 ; Sales et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[51], Mycobacterium sp. PH-06 [39] Afipia [52,53], Dokdonella [53], Xanthobacter [26,54] and Flavobacterium [3]. However, in this study, a mixed culture was tested with two types of bioreactors, CSTR and PFR, on the lab scale.…”
Section: Modelling Approachmentioning
confidence: 99%
“…[41]. Moreover, Dokdonella sp is reported as a microorganism able to degrade ethers [42]. Enzymes produced by these bacteria could be involved in the degradation of dyes and may be responsible for the weak retention of colours.…”
Section: Next-generation Sequencingmentioning
confidence: 99%